Human Resource Development Strategies for Enhancing Digital Well-Being among Islamic Education Teachers - Miftahul a'la; Sri Minarti (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Although digital well-being has received increasing attention, research on Human Resource Development (HRD) strategies to enhance digital well-being among Islamic education teachers remains limited. This study aims to develop HRD strategic steps based on planning, organizing, actuating, and controlling (POAC) that integrate digital well-being with Islamic values. A qualitative case study approach was employed at SMP Negeri 2 Padangan, involving five key informants selected purposively, consisting of two Islamic education teachers, the principal, and two vice principals. Data were collected through a systematic literature review, semi-structured interviews, and observations, then analyzed using interactive thematic analysis and triangulation. The findings reveal three key issues: connectivity invasion that blurs work–life boundaries and creates telepressure, a gap between technical digital training and teachers’ well-being needs, and personal spiritual coping practices that remain institutionally unintegrated. Based on these findings, the study proposes four HRD interventions: digital workload risk assessment, an Islamic “right to disconnect” policy, a Spiritual Digital Coaching program combining stress management with muraqabah and muhasabah, and a holistic well-being-based performance evaluation. These findings contribute to digital well-being theory in faith-based education by integrating Islamic ethical principles, including ḥifẓ al-nafs, wasaṭiyyah, and qudwah, into HRD strategy. The study concludes that safeguarding teachers’ digital well-being is both a spiritual and strategic necessity and recommends that educational institutions adopt POAC-based HRD strategies to build a sustainable professional culture. Future research should operationalize and test these strategies and develop context-specific digital well-being assessment tools.